1998
DOI: 10.1161/01.str.29.2.380
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Physical Activity and Ischemic Stroke Risk

Abstract: Background and Purpose-Physical activity reduces the risk of premature death and cardiovascular disease, but the relationship to stroke is less well studied. The objective of this study was to investigate the association between leisure-time physical activity and ischemic stroke in an urban, elderly, multiethnic population. Methods-The Northern Manhattan Stroke Study is a population-based incidence and case-control study. Case subjects had first ischemic stroke, and control subjects were derived through random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
243
1
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 339 publications
(260 citation statements)
references
References 56 publications
10
243
1
6
Order By: Relevance
“…Reduced physical activity levels after stroke may also contribute to poor cardiovascular-metabolic health and an increased risk for recurrent cerebrovascular events [15]. Physical fitness and cardiovascular health are integrally related, with epidemiological studies indicating physical inactivity is associated with increased risk for incident stroke [16].…”
Section: Problem Of Poststroke Deconditioningmentioning
confidence: 99%
“…Reduced physical activity levels after stroke may also contribute to poor cardiovascular-metabolic health and an increased risk for recurrent cerebrovascular events [15]. Physical fitness and cardiovascular health are integrally related, with epidemiological studies indicating physical inactivity is associated with increased risk for incident stroke [16].…”
Section: Problem Of Poststroke Deconditioningmentioning
confidence: 99%
“…Evidence is accumulating that stroke risk can be reduced with regular leisure-time physical activity in multiethnic individuals of all ages and both sexes. 28 Recently, the association between baseline cardiorespiratory fitness and stroke mortality was investigated in 16 878 apparently healthy men, aged 40 to 87 years, with the Aerobics Center Longitudinal Study database. 25 During an average of 10 years of follow-up, men in the moderate-and high-fitness groups had a 63% and 68% lower risk of stroke death, respectively, than men who were in the lowest-fitness group at baseline.…”
Section: Goals Of Prescribed Physical Activity/exercisementioning
confidence: 99%
“…48 -50 Evidence is accumulating that stroke risk can be reduced with regular leisure-time physical activity in multiethnic individuals of all ages and both sexes. 28 Evidence now suggests that the exercise trainability of stroke survivors may be comparable to that of age-matched healthy counterparts. 10,16 -18,56 Extrapolation of what is known about the training effects of regular exercise by able-bodied individuals suggests that certain levels of exercise that are achieved during many stroke rehabilitation programs may improve aerobic fitness.…”
Section: Benefits Of Aerobic Conditioningmentioning
confidence: 99%
“…The beneficial effects of physical activity have also been documented for stroke. [165][166][167][168][169][170][171][172][173] The Framingham Heart Study, Honolulu Heart Program, and Oslo Study have shown the protective effect of physical activity for men. 166 -168 For women, the Nurses' Health Study and Copenhagen City Heart Study demonstrated an inverse association between level of physical activity and stroke incidence.…”
Section: Physical Inactivitymentioning
confidence: 99%
“…Additional protection was observed with increasing duration of exercise; however, the prevalence of such activities in the elderly was quite low. 172 The protective effect of physical activity may be mediated in part through its role in controlling various known risk factors for stroke, such as hypertension, 175 cardiovascular disease, 176 diabetes, 177 and body weight. Other biological mechanisms are also associated with physical activity, including reductions in plasma fibrinogen and platelet activity, as well as elevations in plasma tissue plasminogen activator activity and HDL concentrations.…”
Section: Physical Inactivitymentioning
confidence: 99%